Kontribusi Penempatan terhadap Motivasi Kerja Pegawai Dinas Pendidikan dan Kebudayaan Kabupaten Lima Puluh Kota - Vani Maulina; Ahmad Sabandi; Syahril Syahril (Universitas Negeri Padang, 2020)
This research aim to get information about employee placement by head contribution to work motivation in Dinas Pendidikan dan Kebudayaan Kabupaten Lima Puluh Kota.The populationis87 employees of Dinas Pendidikan dan Kebudayaan Kabupaten Lima Puluh Kota District.The samples takenby using simple random sampling technique for 74 people.The instrument usedin this studyis a questionnaire.Data analysed by using correlation technique and regresi preceded normalitas test, homogenitas test, linearitas test and also continued with searching the level of employee placement by head variable contribution to work motivation with result 12,4%, while rest 87,6% influenced by other factor